Impact of Guidance and Multitasking on Manual Dexterity Skills in Dentistry - El-Kishawi, Mohamed; Khalaf, Khaled; Murray, Colin; Odeh, Ruba; Winning, Tracey (European Journal of Dentistry, 2022)
Objectives This study investigated the effect of learning by observation on the development of fine motor skills related to endodontic manual instrumentation. We evaluated if learning by observation with guidance had any influence upon operator performance under tense or taxing conditions.Materials and Methods Dental students prepared standardized simulated root canals of varying morphology. Learning involved silent video with hand guidance (n = 23), audiovisual combined with oral instructions (n = 23), or silent video (n = 13). Undergraduates who previously completed conventional preclinical endodontics provided comparative data as a control group (n = 16). During investigations, a root canal of a lower molar plastic tooth was shaped, beginning with a primary task, and followed by multitasking conditions. The performance of the students was assessed by evaluating the accuracy of dental canal shaping and time taken to complete the task.Statistical Analysis Differences were analyzed using ANOVA (p < 0.05).Results Performance was similar during learning between the three experimental groups. Accuracy of the performance did not differ within each group for the two tests nor between the groups at each test (p > 0.05).Conclusions These findings demonstrated that performance subsequent to learning by observation without instructions was comparable to learning with instructed observation. The results also identified that the performance of the experimental group (1.5- to 2-hour practice) was comparable with the conventional control group (15- to 20-hour practice). Alternative approaches to learning dexterity skills in dentistry may provide improved outcomes, especially in demanding situations.
Keywords: motor skills; manual dexterity; learning by guidance; simulation; dentistry